ONTOLOGY AND METADATA IN SEMANTIC ANALYSIS OF DATABASES: PRINCIPLES AND APPLICATIONS - Muxtarov Rustam Axtam o‘g‘li (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the use of ontology and metadata in the semantic analysis of databases. Ontologies provide a formal representation of domain knowledge, while metadata describes the structure, content, and context of data elements. Combining these approaches enables more effective semantic analysis, knowledge extraction, and intelligent querying of database systems. The paper highlights the principles, methodologies, and practical applications of ontology- and metadata-driven semantic analysis, demonstrating its significance for improving data consistency, interoperability, and decision-making in modern information systems.